Atributivne lastnosti lune v ukrajinskih in angleških ljudskih ugankah - Luchechko, Tetiana (Slavia Centralis, 2021)
The paper attempts to provide a contrastive study of the riddle manifestation of the Ukrainian and English conception of the Moon. The article examines the corpus of Ukrainian and English riddles for the Moon found mainly in major Ukrainian and English riddle collections – Riddles (1962) edited by I. Berezovskyi and English Riddles from Oral Tradition (1951) edited by A. Taylor. It focuses on tracing the common and national features of Moon codifiers (associative parallels) as well as their motivation verbalised in riddle corpora under comparison. The Ukrainian and English conception of the Moon is reconstructed through its similar attributive features of the encoded object and its codifiers explicitly and/or implicitly represented in riddles from oral tradition.